A method of implanting combinational hardware Trojan based on evolvable hardware. (July 2021) - Liu, Lijun; Wang, Tao; Wang, Xiaohan; He, Tianyu
Highlights: Compared with the general method, it is not to add hardware Trojan, but to modify the original circuit to generate Trojan function. The hardware Trojan designed by EHW has little effect on the number of the logic gates and power consumption of the original circuit, and has good concealment. According to the symmetric value and similar value to evaluate the difficulty of evolution, choose the hardware Trojan that is easy to evolve. Abstract: In order to reduce the impact of Hardware Trojan (HT) implantation on the original circuit power consumption, a method using Evolvable Hardware (EHW) to implant combinational HT is proposed. First, the truth table of the original circuit is modified according to the category of HT. Secondly, the symmetric value and similar value are used to evaluate the difficulty degree of evolution, and the truth table which is easy to evolve is selected for evolution. Finally, from the various circuits generated by evolution, the circuit close to the number of logic gates and power consumption of the original circuit is selected to replace the original circuit. The obtained circuit not only includes the HT function, but also improve the anti-power detection ability. According to the experimental results, the HT implanted by EHW has smaller power consumption difference than the HT implanted by general method, and has stronger anti-power detection ability. Graphical abstract: Image, graphical abstract